1980
DOI: 10.1111/j.1600-0528.1980.tb01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health of adolescent and adult Australian Aborigines

Abstract: A pilot survey of oral health included 83 adolescent and adult Aborigines (41 M, 42 F, range 16--70 years, mean age 37.3 years), resident in fringe settlements around the far western New South Wales towns of Brewarrina and Walgett (fluoride in water less than or equal to 0.02--0.26 parts/10(6)). Dental caries prevalence (mean DIMFT per person) increased from 17.1 at 20 years to 10.7 at 35 years and declined to 14.6 by the age of 50 years and over. Oral hygiene (OHI) was poor overall and deteriorated with age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 9 publications
2
18
1
Order By: Relevance
“…8 The limited studies available suggest that the oral health of Indigenous Australians is deteriorating. Schamschula et al 9 found that oral health had deteriorated among adolescents and young adults in Brewarina and Walgett in New South Wales and more recent studies have confirmed the trend. 10,11 These studies not only indicate an increase in total disease experience but a large proportion of the caries experience remains untreated.…”
Section: Introductionmentioning
confidence: 95%
“…8 The limited studies available suggest that the oral health of Indigenous Australians is deteriorating. Schamschula et al 9 found that oral health had deteriorated among adolescents and young adults in Brewarina and Walgett in New South Wales and more recent studies have confirmed the trend. 10,11 These studies not only indicate an increase in total disease experience but a large proportion of the caries experience remains untreated.…”
Section: Introductionmentioning
confidence: 95%
“…Until recently, several populations living in isolated areas of the world kept their ancestral ways of life (for instance, many African tribes, Inuits, South American Indians, Melanesian, Polynesian) under conditions of perfect adaptation to their environments and diets (Donnelly et al, 1977;Mayhall, 1977;Pedersen, 1971;Schamschula et al, 1980;Walker & Hewlett, 1990). Bacteriologic analyses of their dental plaques, although not extensive, show cariogenic species, but those individuals are still developing few or no caries.…”
Section: Diet and The "Main Villain" In The Raise Of Caries Throughoumentioning
confidence: 99%
“…A similar "bell-shaped" caries distribution was observed by Maat and Van der Velde (1987), where the highest prevalence of caries was recorded in individuals with light-to-moderate dental wear. The diet of Australian aboriginal populations has been reported to be low in cariogenic substances (Davies et al 1997), but caries prevalence is comparatively high (from 15 to 48%) (Barrett and Williamson 1972;Schamschula et al 1980;Pascoe and Kim Seow 1994). The comparatively low prevalence of caries in Ngaraangbal tribes was related to a high proportion of marine foods (Elvery et al 1998).…”
mentioning
confidence: 99%